The physical, chemical, and microbiological stability of chloramphenicol ophthalmic solution - Tauwfik Salih; Idris El-Mahdi (Libyan International Medical University Journal)
Aims: The aim of this work is to “predict” the remaining shelf-life of chloramphenicol (CH) eye drops, commercially marketed, using the theoretical “Longland–Rowbotham model,”” followed by confirmation of findings by practical means. Materials and Methods: The methods used for the evaluation of CH-eye drops included the assay of the active ingredient, sterility testing, and minimum inhibitory concentration (MIC) determination using official methods during 6 months stability study at variable temperatures (4, 25°C). Furthermore, a 3-month accelerated stability study was carried out. Statistical analysis tests included Student's t-test and analysis of variance. Results: The prediction model indicated that in pessimistic conditions, the remaining shelf life was reduced to a merely 1 month following production (this is versus the 2 years expiration date given by manufacturer). However, the samples analyzed throughout a 6-month stability study revealed that storing CH solution at 4°C or 25°C does not produce any statistical difference regarding drug content, MIC, or sterility. Accelerated stability studies for 3 months period showed that only after 2 months from storage at 55°C the drug will start to degrade and a statistical difference could be observed. Conclusion: Storing CH-eye drops at room temperature for up to 6 months appears to have no effect on the stability of this antibiotic.